FORMULASI EMULGEL EKSTRAK LENDIR IKAN GABUS (Channa striata) UNTUK LUKA DIABETES - Batenia, Putri (Politeknik Tiara Bunda, 2022)
Corkfish (Channa striata) is a type of freshwater fish that has a high protein content of albumin which plays an important role in the proliferation phase in the process of wound healing. The purpose of this study was to find out that Corkfish mucus extract (Channa striata) was able to heal the wounds of Diabetes Mellitus and find out the concentration of gelling agent that is good in the absorption of nutritious substances. This study used a sample of Corkfish mucus extract (Channa striata) made in emulgel preparations for diabetic with emulgel preparations during 14 days with a wound length of 2 cm. Based on the results of the data obtained using One way ANOVA, the results showed that it can significantly heal wounds with the occurrence of the process of maturation in the wound